Traction endurance biomechanical study of metallic suture anchors at different insertion angles - Azato,Flávia Namie (2003)
The suture anchors' insertion angle and its traction resistance are the main subjects of this study. Twenty trials were realized using threaded suture anchors in four diferents angulations (30º /45º /60º /90º) in human bone (distal femur) and another twenty trials in artificial bone (SawboneTM). The anchors were pulled out being tractioned uprightly from its bone surface by a Kratos Universal test machine. The human bone results found no relation between the main subjects of this study, so whithout statistical value. On the other hand at the artificial bone the insertion angle of 90º beared more traction, being statistically significant compared to the other angles.